Effect of NPC1L1 and HMGCR Genetic Variants With Premature Triple-Vessel Coronary Disease - Xueyan Zhao (Frontiers Media S.A., 2021)
Background: Both Niemann-Pick C1-like 1 (NPC1L1) and 3-hydroxy-3-methylglutaryl-coenzyme A reductase (HMGCR) play a key role on dyslipidaemia. We aim to evaluate whether NPC1L1 and HMGCR genetic variants are associated with susceptibility of premature triple-vessel disease (PTVD).Methods: Four single-nucleotide polymorphisms (SNPs) (rs11763759, rs4720470, rs2072183, and rs2073547) of NPC1L1; and three SNPs (rs12916, rs2303151, and rs4629571) of HMGCR were genotyped in 872 PTVD patients (males ≤ 50 years old and females ≤ 60 years old), and 401 healthy controls.Results: After adjusting for age and sex, rs12916 of HMGCR was associated with the risk of PTVD in dominance model [odds ratio (OR) = 1.68, 95% confidence intervals (CI): 1.29–2.18, P < 0.001], recessive model (OR = 1.43, 95% CI: 1.08–1.90, P = 0.013) and codominant model (OR = 1.38, 95% CI: 1.17–1.63, P < 0.001); meanwhile, rs4720470 of NPC1L1 was related to increased risk of PTVD in recessive model (OR = 1.74, 95% CI: 1.14–2.74, P = 0.013). Patients who carried both variant rs4720470 and rs12916 also had the risk of PTVD (P < 0.001); however, there were no correlation between these SNPs and the SNYTAX score (all P > 0.05).Conclusions: This is the first report that rs4720470 is a novel polymorphism of the NPC1L1 gene associated with PTVD, and rs12916 of HMGCR gene appears to be a strong genetic marker of PTVD. Our study may improve the early warning, therapeutic strategies and drug development of PTVD.